2017
DOI: 10.47672/ajf.267
|View full text |Cite
|
Sign up to set email alerts
|

Review of Microfinance and Women Empowerment in Ethiopia

Abstract: Purpose: The purpose of this study was to review the role of microfinance and empowering women in Ethiopia Findings: According to findings of different authors microfinance is providing financial services to unemployed and low income individuals or groups who would have no access to formal banking services. It has positive impact on the living standard of the poor people in particular and alleviating poverty in their household in general. It is not only undermining poverty in the country, but also empowering w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Gobezie (2017) also added that after participating in MFI women learn and began saving both in the MFI and other banks. Moreover, Meron Haileselassie (as cited in Kabeta, 2017) found that the study indicated that the income and saving levels of the majority of the clients have increased after the delivery of microfinance.…”
Section: Improvement In the Skills Of Savingmentioning
confidence: 95%
See 2 more Smart Citations
“…Gobezie (2017) also added that after participating in MFI women learn and began saving both in the MFI and other banks. Moreover, Meron Haileselassie (as cited in Kabeta, 2017) found that the study indicated that the income and saving levels of the majority of the clients have increased after the delivery of microfinance.…”
Section: Improvement In the Skills Of Savingmentioning
confidence: 95%
“…For instance, studies conducted on ACSI by Gobezie (2017) and Deribie et al (2013) found that microfinance is a good strategy to mitigate poverty and it creates an opportunity for the marginalised segment of the population in accessing to finance. On the other hand, Meron Hailesellassie (as cited in Kabeta, 2017) conducted research in Addis Ababa on the role of microfinance in empowering women which shows that, although women benefited in economic empowerment from MFI interventions, women's workload increased as a result of MFI, spent income for family purpose and also it does not make a significant change for women in political empowerment.…”
Section: Problems Mfi Identified In the Ethiopian Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Microfinance institutions found to decisive way outs from the vicious circle of poverty, particularly for the rural and urban poor, particularly in a country like Ethiopia where many people live barely below the absolute poverty line (Kabeta, 2017). The microfinancing industry of Ethiopia is escalating in the face of the growing deep concerns for inflation and low-interest rate in the microfinance industry affecting the financial health and viability of MFIs.…”
Section: Introductionmentioning
confidence: 99%